Formulation and evaluation of bilayer matrix tablets of Amlodipine besylate and metoprolol Succinate - SELVI ARUNKUMAR; DR. L. SRINIVAS; DR. D. SATYAVATI; DR. C. EMMANUEL (International Journal of Pharma and Bio Sciences, 2018)
The present study is an attempt to develop bilayer matrix tablets containing Amlodipine Besylate and Metoprolol Succinate with immediate release for Amlodipine and sustained release for Metoprolol. Superdisintegrants such as sodium starch glycolate and Croscarmellose sodium were evaluated for immediate release of Amlodipine and polymers HPMC K100M and K4M for sustain release of Metoprolol. Preformulation studies were performed prior to compression. The compressed bilayer tablets were evaluated for weight variation, dimension, hardness, friability, drug content and in vitro drug release using USP dissolution apparatus type 2 in0.01N HCl and phosphate buffer pH 6.8.All the pre and post-compression parameters were found to be within the acceptable limits. The results of dissolution show that the formulations F1, F5&, F10 were the best of all immediate and sustained release layer batches. The release kinetics of Metoprolol Succinate was subject to curve fitting analysis in order to find the best fit kinetic model. The regression analysis proves that the best formulations follow zero order release. The data for stability studies infer no considerable change in drug content and dissolution rates as per ICH guidelines. Hence a novel Bilayer tablet formulation of Amlodipine Besylate and Metoprolol Succinate was successfully developed by combining both immediate (IR) and sustained (SR) release layers.